Antimicrobial peptides from the hemolymph of the prawn Macrobrachium rosenbergii - Ravichandran, Samuthirapandian; Jeyalakshmi, Singaram; Sudha, Sathasivam; Anbuchezhian, Ramasamy (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">The study was carried out to find the antimicrobial activity of hemolymph of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Macrobrachium <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">rosenbergii <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">and to evaluate the antimicrobial compounds. <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">The highest inhibition against <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">Staphylococcus aureus, Lactobacillus vulgaris<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB"> and <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">Klebsiella pneumonia <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">(12 mm) and antifungal activity was observed only against <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">Fusarium moniliforme <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">(11 mm). <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Antimicrobial peptide was characterized in molecular size ranging from 22 to 91KDa with antimicrobial activity against various infectious pathogens. <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">Hemolymph plays a vital role in the disease prevention in crustaceans and there is no report on antimicrobial activities of the prawn <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-GB; mso-ansi-language: en-GB; mso-bidi-language: ar-SA;" lang="en-GB">M. rosenbergii.